Pengaruh Kualitas Makanan Dan Kewajaran Harga Terhadap Kepuasan Pelanggan Generasi Milenial Selama Masa Pandemi Covid-19 - Nonot Yuliantoro; Erinna Gracia; Jessica Novia (Journal FAME: Journal Food and Beverage, Product and Services, Accomodation Industry, Entertainment Services, 2021)
Abstract The purpose of this study was to analyze and examine the effect of food quality and the fairness of the XYZ restaurant prices in Alam Sutera on the customer satisfaction of the millennial generation. This research is a quantitative study using a survey method. In this study, the population is the millennial generation who live in the Tangerang and Jakarta area with a vulnerable age of 18-38 years as customers at XYZ Alam Sutera Restaurant. The sample was taken randomly as many as 200 respondents with the online purposive sampling technique. Data collection was carried out during the COVID-19 pandemic using a Likert scale 1-5 instrument. The data analysis technique used instrument test, descriptive analysis, hypothesis testing using validity test, reliability test, determination coefficient test, T test and F test as well as multiple linear regression, classical assumption test. The data obtained were analyzed through the SPSS version 25.0 program. The results of this study indicate that food quality has a significant positive effect on customer satisfaction. A significant positive relationship also exists in price reasonableness and customer satisfaction. Keywords: Food Quality, Price Fairness, Customer Satisfaction, Millennial Generation.